2009
DOI: 10.1152/jn.91069.2008
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Visuomotor Rotation and Force Field Perturbation Is Correlated to Different Brain Areas in Patients With Cerebellar Degeneration

Abstract: Although it is widely agreed that the cerebellum is necessary for learning and consolidation of new motor tasks, it is not known whether adaptation to kinematic and dynamic errors is processed by the same cerebellar areas or whether different parts play a decisive role. We investigated arm movements in a visuomotor (VM) rotation and a force field (FF) perturbation task in 14 participants with cerebellar degeneration and 14 age- and gender-matched controls. Magnetic resonance images were used to calculate the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
166
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 47 publications
16
166
2
1
Order By: Relevance
“…However, it is possible that the discrepancy between their findings and our findings may be attributed to some methodological differences, such as the type of perturbation (dynamic vs. visuomotor) and the number of targets. In fact, it has been suggested that visuomotor and dynamic adaptations are subserved by distinct neural mechanisms (e.g., Krakauer et al 1999;Rabe et al 2009;Wang and Sainburg 2004). Given that the sensorimotor conditions employed in the two studies (dynamic adaptation in Malfait and Ostry's study, visuomotor adaptation in the present study) are different, further research may be needed to ensure whether the effect of awareness on interlimb transfer depends on the sensorimotor nature of a given task.…”
Section: Discussionmentioning
confidence: 76%
“…However, it is possible that the discrepancy between their findings and our findings may be attributed to some methodological differences, such as the type of perturbation (dynamic vs. visuomotor) and the number of targets. In fact, it has been suggested that visuomotor and dynamic adaptations are subserved by distinct neural mechanisms (e.g., Krakauer et al 1999;Rabe et al 2009;Wang and Sainburg 2004). Given that the sensorimotor conditions employed in the two studies (dynamic adaptation in Malfait and Ostry's study, visuomotor adaptation in the present study) are different, further research may be needed to ensure whether the effect of awareness on interlimb transfer depends on the sensorimotor nature of a given task.…”
Section: Discussionmentioning
confidence: 76%
“…However, visuomotor adaptation is known to be subserved by both explicit and implicit processes (Mazzoni and Krakauer 2006;Taylor et al 2014), while adjustment of grip and load forces during lifting seems to be largely implicit, evidenced by the fact that the size-weight illusion persists after appropriate motor adjustments have been made (Flanagan and Beltzner 2000). These tasks also differ in their dependence on the cerebellum; patients with cerebellar degeneration are impaired in adapting to visuomotor rotations (Martin et al 1996;Maschke et al 2004;Smith and Shadmehr 2005;Chen et al 2006;Tseng et al 2007;Rabe et al 2009b) but show no apparent deficit in adjusting grip and load forces to objects of unusual densities (Rabe et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Error-dependent adaptation of movements is generally thought to require integrity of the cerebellum (Martin et al 1996;Maschke et al 2004;Rabe et al 2009;Smith and Shadmehr 2005). Complex spikes (CSs) that are generated by climbing fiber inputs onto Purkinje cells of the cerebellum are considered to be the biological representation of an error signal (Kitazawa et al 1998).…”
mentioning
confidence: 99%
“…Behavioral studies suggest that learning from visual and proprioceptive errors may occur independently (Bock and Thomas 2011;Krakauer et al 1999;Pipereit et al 2006). Furthermore, a recent study of people with cerebellar damage demonstrated that adaptation in these two paradigms relied on different regions of the cerebellum (Donchin et al 2012;Rabe et al 2009). Thus it is important to consider the relative contributions of visual and proprioceptive error and understand how the two interact.…”
mentioning
confidence: 99%